2022
DOI: 10.2147/jmdh.s295478
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Multidisciplinary Health Care Team in the Management of Patients with Systemic Sclerosis

Abstract: Systemic sclerosis (SSc) is a rare connective tissue disease characterised by immune dysfunction, vascular damage and fibrosis affecting the skin and multiple internal organs. The clinical spectrum of SSc is wide and its manifestations may lead to severe morbidity and mortality, in addition to a great impact on patients’ quality of life. Due to the multifaceted clinical manifestations of SSc, its management requires a combined expertise of different medical specialists to guarantee an adequate disease control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…The overall follow-up assessment of a patient with SSc-ILD should go beyond the control of lung functionality and drug toxicities: it should consider a multidisciplinary team evaluation, in collaboration with other specialists, including pulmonologists and radiologists. 27 Both specialists are pivotal in the close collaboration with the rheumatologists, to identify clinically meaningful progression, rule out other causes for the clinical worsening of a patient, and to choose the optimal drug strategy. Bronchoalveolar lavage, for example, represents a useful instrument to rule out infections and other concomitant lung pathologies, requiring pulmonologist experience and expertise.…”
Section: Safety and Additional Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall follow-up assessment of a patient with SSc-ILD should go beyond the control of lung functionality and drug toxicities: it should consider a multidisciplinary team evaluation, in collaboration with other specialists, including pulmonologists and radiologists. 27 Both specialists are pivotal in the close collaboration with the rheumatologists, to identify clinically meaningful progression, rule out other causes for the clinical worsening of a patient, and to choose the optimal drug strategy. Bronchoalveolar lavage, for example, represents a useful instrument to rule out infections and other concomitant lung pathologies, requiring pulmonologist experience and expertise.…”
Section: Safety and Additional Considerationsmentioning
confidence: 99%
“…In the meantime, multidisciplinary team care involving experts from rheumatology, pulmonology, and radiology is recommended to offer SSc-ILD patients high-quality care following the most recent insights. 27…”
Section: Introductionmentioning
confidence: 99%
“…Questions regarding the preference for upfront or sequential combined immunosuppressive and antifibrotic therapy or the addition of biologics, as is common in other rheumatic diseases, remain areas for further research. In this regard, several studies have reported that combining MMF with nintedanib provides the best scenario for preserving lung function in patients who show disease progression while on a single immunomodulatory agent [3,18,[59][60][61]. The optimal therapeutic strategy for managing SSc-ILD patients, including those with a PF phenotype, remains to be determined, particularly given the heterogeneity of the disease.…”
Section: Ppf Treatment In Ssc-ild Patientsmentioning
confidence: 99%
“…Members of MDTs can effectively deal with several aspects of the disease that impact the prognosis and quality of life of individuals with SSc, improving communication and empowering them. In this regard, a previous systematic review of the effectiveness of non‐pharmacological interventions in SSc identified a total of 23 articles published between 1990 and 2014, of which 9 were randomized controlled trials (RCTs) 23 . Researchers assessed various oral health interventions, MDT care and diverse therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…A non-pharmacological intervention can be defined as a treatment not involving a registered medication and can be used alone randomized controlled trials (RCTs). 23 Researchers assessed various oral health interventions, MDT care and diverse therapeutic approaches. In addition to this review, 3 more recent systematic reviews have been published 20,24,25 exploring the effects of nonpharmacological interventions on SSc individuals.…”
Section: Introductionmentioning
confidence: 99%